Does Foreign Language Proficiency Foster Migration of Young Individuals within the European Union? - Ainhoa Aparicio Fenoll; Zoë Kuehn (Institute for the Study of Labor (IZA), 2014)
Speaking the language of the host country eases migrants' integration and tends to boost their economic success in the country of destination. However, the decision to acquire language skills may in itself be determined by the intention to migrate. In addition, conditional on being a migrant, the relation between language skills and migrants' integration and economic success goes both ways. Using data on the study of foreign languages during compulsory education in European countries, we test whether and how much language proficiency determines migration flows across Europe. The European Union with basically unlimited labor mobility and pronounced differences in youth unemployment rates provides an ideal testing ground for our hypothesis. We find that speaking the language of a country increases the likelihood to migrate to that country almost fivefold.
Keywords: J61; I20; F22; 330; migration; language proficiency; return to skills; education